Cracking Behavior of Ceramsite Aerated Concrete Block Infill Wall in the Coastal Areas - Ruige Li; Huadong Cui; Lingchao Ding; Haiping Ni; Shangquan Xu; Huiling Wu (International Journal of Concrete Structures and Materials)
Abstract Ceramsite aerated concrete blocks (CACB) are widely used in reinforced concrete frame infill walls due to their green, energy-saving, waste utilization, and thermal insulation characteristics. Investigations into building projects in areas with low seismic intensity and frequent typhoons have found that the cracking of CACB infill walls is severe, which hinders the use of this material. This article was dedicated to studying the reasons and development process of cracks in CACB infill walls, and proposing solutions. First, a 13 story framework building was analyzed using PKPM software to study the inter-story drift ratio under local reference wind pressure and gust wind pressure. Then, three full-scale models were made for quasi-static tests under horizontal loads to study the correlation between inter-story drift ratio and infill wall cracking. Experimental studies have shown that the inter-story drift ratio was 1/2149 and 1/2347 for infill wall frames with and without windows, respectively, when CACB infill walls cracked. Comparing PKPM analysis and experimental results, it could be seen that when the building was subjected to local reference wind pressure, the inter-story drift ratio was 1/2433, which was smaller than the cracking inter-story drift ratio. When subjected to the wind pressure corresponding to the gust wind, the structural deformation was much greater than the cracking inter-story drift ratio. Therefore, it could be concluded that the main reason for diagonal cracks in CACB infill walls was the unreasonable use of reference wind pressure in current design. To avoid the diagonal cracks, gust wind pressure should be used as the horizontal load instead of reference wind pressure in design. Simultaneously to improve both structural construction measures and material crack resistance to avoid cracking of CACB infill walls.